Pengaruh Pengetahuan Pajak, Kesadaran Wajib Pajak, dan Moralitas Pajak terhadap Kepatuhan Wajib Pajak dengan Budaya Pajak sebagai Variabel Moderasi - Neyla Safitri; David Pangaribuan; Panata Bangar Hasioan Sianipar (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study aims to test and analyze the influence of tax knowledge, taxpayer awareness, and tax morality on taxpayer compliance and tax culture as a moderating variable. The method used in this study is a quantitative method with a survey approach. The object of this study is individual taxpayers in Bekasi Regency. In this study, the sample data was 120 respondents. Data were collected by distributing questionnaires to 120 respondents. The results show that tax knowledge and taxpayer awareness have a positive effect on taxpayer compliance, while tax morality has no effect. Tax culture is able to moderate the effect of tax knowledge on taxpayer compliance, and is unable to moderate the effect of taxpayer awareness and tax morality on taxpayer compliance.